Employing Broadly Neutralizing Antibodies as a Human Immunodeficiency Virus Prophylactic & Therapeutic Application - Ding, Chengchao; Patel, Darshit; Ma, Yunjing; Mann, Jamie F. S.; Wu, Jianjun; Gao, Yong (Frontiers in Immunology, 2021)
Despite the discovery that the human immunodeficiency virus (HIV) is the pathogen of acquired immunodeficiency syndrome (AIDS) in 1983, there is still no effective anti-HIV vaccine. The major obstacle to the development of HIV vaccine is the extreme viral diversity. Nonetheless, critical advances in this area have been made and identified a number of broad and potent neutralizing anti-HIV antibodies (bNAbs), and in novel strategies on how to utilize these assets as an efficacious preventive and/or therapeutic intervention. Here we summarize the recent development of bNAbs and its application in HIV acquisition prevention as well as discuss the innovative approaches being used to try to convey protection within individuals at risk and being treated for HIV infection.